A Mechanistic Rationale Approach Revealed the Unexpected Chemoselectivity of an Artificial Ru-Dependent Oxidase: A Dual Experimental/Theoretical Approach - Lopez, Sarah; Mayes, David Michael; Crouzy, Serge C.; Cavazza, Christine; Lepretre, Chloe; Moreau, Yohann; Burzlaff, Nicolai; Delapierre, Caroline Marchi; Menage, Stephane (ACS Catalysis, 2020)
Artificial enzymes represent an attractive alternative to design abiotic biocatalysis. EcNikA-Rul, an artificial metalloenzyme developed by embedding a ruthenium-based catalyst into the cavity of the periplasmic nickel-binding protein NikA, was found to efficiently and selectively transform certain alkenes. The objective of this study was to provide a rationale on the enzymatic function and the unexpected substrate-dependent chemoselectivity of EcNikA-Rul thanks to a dual experimental/computational study. We observed that the de novo active site allows the formation of the terminal oxidant via the formation of a ruthenium aquo species that subsequently reacts with the hypervalent iodine of phenyl iodide diacetic acid. The oxidation process relies on a Ru-IV = 0 pathway via a two-step reaction with a radical intermediate, resulting in the formation of either a chlorohydrin or an epoxide. The results emphasize the impact of the protein scaffold on the kinetics of the reaction, through (i) the promotion of the starting oxidizing species via the exchange of a CO ligand with a water molecule; and (ii) the control of the substrate orientation on the intermediate structures, formed after the Ru-IV= 0 attack. When a C alpha attack is preferred, chlorohydrins are formed while an attack on C beta leads to an epoxide. This work provides evidence that artificial enzymes mimic the behavior of their natural counterparts.
CRIS-Team WoS Importer:2020-06-09